2022
DOI: 10.1029/2021jd035058
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Role of Atmospheric and Surface Albedo on Polar Amplification Using Satellite Observations and CMIP6 Model Output

Abstract: Polar amplification (PA) refers to the phenomenon where an external radiative forcing, such as changes in greenhouse gases (GHGs) and solar variability (Collins et al., 2013;Gregory & Webb, 2007;Gregory et al., 2004) causes a stronger warming effect in the polar regions than the rest of the Earth (Manabe & Wetherald, 1975;Trenberth et al., 2007). PA can be quantified by the PA factor (fPA) which is the ratio between temperature change in the high latitudes to the temperature change in the low-to mid-latitudes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The models used and their corresponding variables are shown in Table S1 in Supporting Information S1. According to Donohoe and Battisti (2011) and Södergren and McDonald (2022), the surface albedo can be calculated using a simplified equation based on a simple radiation model, that is, the albedo is equal to the ratio of surface downwelling shortwave radiation (rsds) to surface upwelling shortwave radiation (rsus).…”
Section: Cmip6mentioning
confidence: 99%
“…The models used and their corresponding variables are shown in Table S1 in Supporting Information S1. According to Donohoe and Battisti (2011) and Södergren and McDonald (2022), the surface albedo can be calculated using a simplified equation based on a simple radiation model, that is, the albedo is equal to the ratio of surface downwelling shortwave radiation (rsds) to surface upwelling shortwave radiation (rsus).…”
Section: Cmip6mentioning
confidence: 99%
“…Previous studies found asymmetry in polar amplification, with the Antarctic amplification (AnA) weaker than Arctic amplification [7,8]. Variations in albedo are closely coupled to the strength of polar amplification, and changes in surface albedo are more important relative to changes in the atmosphere, and the opposite sign can be captured in the Arctic [9]. Moreover, changes in surface albedo, cloud cover and atmospheric absorbed shortwave radiation are greater in the Arctic, which is associated with the strong Arctic amplification [9].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in albedo are closely coupled to the strength of polar amplification, and changes in surface albedo are more important relative to changes in the atmosphere, and the opposite sign can be captured in the Arctic [9]. Moreover, changes in surface albedo, cloud cover and atmospheric absorbed shortwave radiation are greater in the Arctic, which is associated with the strong Arctic amplification [9]. The role of stratospheric ozone depletion contributes to the asymmetry, and increased greenhouse gases (GHG) and ozone depletion cause dramatic changes in Southern Hemisphere circulation; the anticipated recovery from ozone depletion may offset the changes that respond to the increasing GHG [10].…”
Section: Introductionmentioning
confidence: 99%
“…Climate model-based analysis drives interpretation and hypotheses of causes behind Arctic Amplification. Several analyses have found sea ice albedo feedbacks are likely driving Arctic Amplification 7 – 12 . The albedo feedback is due to (1) sea ice melting that leads to recession of the ice pack as well as (2) decreasing reflectivity or albedo of the remaining ice due to surface melt 13 18 that changes the snow and ice surface reflectivity as well as forming poorly reflecting melt ponds.…”
Section: Introductionmentioning
confidence: 99%